Evaluation of Estru$ Alert®, Kamar®, and FiL® Tailpaint as aids for detection of estrus - Johnson, Sandra K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three estrus-detection aids were evaluated in beef heifers after synchronization of estrus with a typical melengesterol acetate (MGA)/prostaglandin F2α (PGF) protocol. Devices were applied at the time of PGF administration. Application time was longest for Kamar® patches, intermediate for Estru$ Alert® patches and FiL® Tailpaint, and shortest for controls. The degree to which the detection aids were activated at first observed estrus was dependent on the time of day when first observed and the type of device. A greater proportion of Estru$ Alert® and FiL® Tailpaint devices were 75% to fully activated when first observation of estrus was in the morning, compared with first observations in the afternoon. Time of day did not influence degree of Kamar® patch activation. At breeding, more than 90% of Estru$ Alert® and Kamar® devices were fully activated, whereas more variation in degree of activation was present in heifers with FiL® Tailpaint. Use of detection aids did not increase estrous detection rate or AI pregnancy rates, compared with those of controls when visual observation was intensive. Use of detection aids still requires observation at least twice per day to time inseminations, because the degree of color change/activation is not consistently an indicator of time since onset of estrus.
Keywords: Beef; Estru$ Alert®; Kamar®; FiL® Tailpaint; Estrus